Nkucetelo wa vukriste eku vumbeni ka swimunhuhatwa swa vavasati eka matsalwa ya Sasavona hi D.C. Marivate na Ri Xile hi S.B. Nxumalo - Ubisi, L. L. (University of Limpopo, 2013)
The main aim of this study is to examine the way in which women are explored and explained by authors with special reference to Xitsonga novels, Ri xile by S.B. Nxumalo and Sasavona by D.C. Marivate. The first chapter reveals the general outline of the study, the problem statement, the aim, the importance and its methodology. The most important terms of the study has been explained in this chapter so as to reveal what is expected to be analyzed. Chapter two gives short summary of the novels Sasavona by D.C. Marivate and Ri xile by S.B. Nxumalo which have been examined together with the history of their authors. The definitions of the word characters and characterization have been included and defined in this chapter. In this chapter, the novels which have been selected to be analysed have been analysed. Chaper three explains, defines and analysed the themes of selected two novels. The definitions of theme has been given in this chapter. This definitions will make readers to understand what theme is. Chapter four deals with the setting or milieu of the above mentioned novels. Chapter five deals with the general summary of this mini-dissertation. The recommendations and recommendations for further research have been indicated in this chapter.
Thesis (M.A.(African Languages)) -- University of Limpopo, 2013
Keywords: Christianity; Women; Tsonga language.; Critical disourse analysis -- Religious aspects; Fiction